1990
DOI: 10.1099/0022-1317-71-8-1661
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Virion Structure, Protein Composition and Genomic DNA of Three Ascovirus Isolates

Abstract: The virions of three ascoviruses isolated from the noctuids Heliothis zea, Spodoptera frugiperda and Trichoplusia ni were compared with respect to their size and structure, protein composition and the size and relatedness of their DNAs. The virions of the isolates from H. zea (HAV) and T. ni (TAV) were allantoid in shape (400x130 nm), enveloped and contained an inner particle which appeared to have an internal lipid bilayer surrounding the DNA core. The virions of the S. frugiperda isolate (SAV) were similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 20 publications
0
39
0
Order By: Relevance
“…The ascoviruses used, SfAV1a and HvAV3c, were isolated initially from the noctuid hosts Spodoptera frugiperda and Heliothis virescens, respectively (Federici et al, 1990). DpAV4 was isolated from its wasp host, Diadromus pulchellus (family Ichneumonidae), and from pupae of its lepidopteran host, Acrolepiopsis assectella (Family Yponeumonidae; Bigot et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…The ascoviruses used, SfAV1a and HvAV3c, were isolated initially from the noctuid hosts Spodoptera frugiperda and Heliothis virescens, respectively (Federici et al, 1990). DpAV4 was isolated from its wasp host, Diadromus pulchellus (family Ichneumonidae), and from pupae of its lepidopteran host, Acrolepiopsis assectella (Family Yponeumonidae; Bigot et al, 1997).…”
Section: Methodsmentioning
confidence: 99%
“…However, the DpAV virion may have a genomic superhelical structure that is not detected in our experiments if the DpAV genome was nicked during DNA purification. It has been suggested that the genomes of Heliotis virescens ascovirus (HAV), Trichoplusia ni ascovirus (TAV) and Spodoptera frugiperda ascovirus (SAV) are linear (Federici et al, 1990), but these ascoviral genomes were not studied by PFGE. The DpAV genome contains 6-8 interspersed repeated sequences of 494 bp.…”
Section: Discussionmentioning
confidence: 99%
“…Inoculated host larvae were reared on an artificial diet. Seven days postinoculation, the haemolymph with vesicles was collected and virions in the vesicles were purified as described by Federici et al (1990). Viral DNA was purified by centrifugation in a CsCl-EthBr gradient for 15 h. Five RENs were used to catalyse cleavage of the viral genomic DNAs prior to agarose gel analysis ; all RENs used were known to yield fewer than 14 fragmentation products.…”
mentioning
confidence: 99%